Indicators for energy performance efficiency certification in the Lithuanian residential buildings - Juodis, Egidijus; Jablonska, Bronia; Uyterlinde, Martine A.; Kaan, Henk F.; van Wees, Mark T. (Journal of Civil Engineering and Management, 2003)
Energy performance certification (EPC) of buildings results in a label for the buildings. Every label has to correspond to a fixed energy consumption per year. Energy consumption taken as a basis for the certification is to reflect efficiency of energy use in buildings and stimulate the occupiers to become more aware of the effect of their behaviour. The method of energy performance efficiency calculation is proposed and numerical values of annual energy consumption are elaborated on the ground of these two aims, European Union requirements and Dutch experience as energy performance efficiency indicators.First Published Online: 26 Jul 2012